An Econometric Analysis of Loan Loss Provisioning Behaviour in Italian Commercial Banks - Fusi, Giulia (2016)
Given the central role that the provisioning system plays during economic crises, this study aims to investigate the Loan Loss Provisioning behaviour of Italian Commercial banks between 2005 and 2015. Firstly, the study will examine the evolution of the performances of Italian banks throughout the period. In addition, scale economies and technical change values will be estimated. Later, the study will analyse the provisioning behaviour of banks testing the incomesmoothing, capital management and business cycle hypotheses. Furthermore, the research aims to verify if the inclusion of the values of cost-efficiency, scale economies and technical change is relevant to model LLPs behaviour.